IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS KONTEKSTUAL UNTUK MENINGKATKAN PEMAHAMAN KONSEP IPA SISWA SEKOLAH DASAR - Nena Puspita Sari; Afrida Hanum (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
This study aims to describe the increased understanding of science concepts by implementing contextual-based Problem Based Learning models on material changes in the shape of objects. This type of research is a quasi-experimental design with one group pretest and posttest. This study uses a quantitative approach. The population in this study were all fifth-grade students at SDN Mutiara, totaling 60 students. The sampling technique was random sampling, so the sample in the study was 30 students in class V-A consisting of 18 female students and 12 male students. Data collection techniques in this study used observation sheets and test items. Data analysis techniques to measure the implementation of the character-based PBL model are carried out operating percentages, and to analyze the understanding of the science concept is carried out using gain. The results showed that the implementation of the character-based PBL model was 82% which was categorized as good. In addition, the results of the analysis of the understanding of the science concept show a gain of 0.6 which is categorized as moderate. So it can be concluded that implementing the character-based PBL model properly it can improve students' understanding of science concepts in class V on the material changes in the shape of objects.